1998
DOI: 10.1016/s0399-1784(98)80019-4
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of arsenic on the continental shelf off the Gironde estuary: Role of phytoplankton in vertical fluxes during spring bloom conditions

Abstract: The arslenic (As) cycle in the marine environment is known to be sensitive to biological activity. Within the scope of the National Coisstal Oceanography Program, we undertook a specific study of the behaviour of this element in a water column on thle continental shelf of the Bay of Biscay off the Gironde estuary during two oceanographic cruises conducted in May 1994 and May 1995. Various chemical forms were measured: arsenite (ASP), arsenate (ASP), monomethylarsenic (MMA), dimethylarsenic (DMA) and dissolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…The flux of DI-As in the Anll贸ns River is small compared with that of other temperate rivers: it is one order of magnitude lower than the flux calculated for the Thames and Adour (Point et al, 2007) whilst it is two orders of magnitude lower than contributions of the Seine (Michel et al, 1999), Loire (Seyler and Martin, 1990), Garonne (Michel et al, 1998), Rhone (Guieu et al, 1991) and Humber (Kitts et al, 1994). Although, to draw a meaningful comparison, this output must by normalized with respect to the area of the river basin; if it is done the DI-As of the Anll贸ns (0.83 kg s -1 km -2…”
Section: Discussion 41 the Fluvial Reservoirmentioning
confidence: 60%
“…The flux of DI-As in the Anll贸ns River is small compared with that of other temperate rivers: it is one order of magnitude lower than the flux calculated for the Thames and Adour (Point et al, 2007) whilst it is two orders of magnitude lower than contributions of the Seine (Michel et al, 1999), Loire (Seyler and Martin, 1990), Garonne (Michel et al, 1998), Rhone (Guieu et al, 1991) and Humber (Kitts et al, 1994). Although, to draw a meaningful comparison, this output must by normalized with respect to the area of the river basin; if it is done the DI-As of the Anll贸ns (0.83 kg s -1 km -2…”
Section: Discussion 41 the Fluvial Reservoirmentioning
confidence: 60%
“…In addition to the well-characterized arsenic species discussed above in estuaries and seawater, there are also reports of unidentified arsenic species in water (58,76,(83)(84)(85)(86). After UV-irradiation of surface water from Uranouchi Inlet, the inorganic and dimethylarsenic concentrations detected with hydride generation rapidly increased (83).…”
Section: Uncharacterized Arsenic Speciesmentioning
confidence: 92%
“…Michel et al reported a difference between the sum of known arsenic species and total arsenic of 13% in the euphotic layer of an estuary (86). These studies suggest that substantial amounts of arsenic remain to be characterized.…”
Section: Uncharacterized Arsenic Speciesmentioning
confidence: 98%
“…A steady-state box model based on the LOICZ Biogeochemical Modelling Guidelines was used to This study 2-8/1991 5-60 (19) 0-42 (5) Xiao et al 1996Xiao et al 10/19802) Zhang 1982 16.4-21.4 (18.2) 4.7-16.0 (8.9) Li et al 1981Bohai Bay, China 8/1980, 198113.3-60.1 (25.4) Li et al 1984Laizhou Bay, China 5,8/2002.5) Ma et al 2003Xiamen Harbor, China 8/1988.7) Li et al 2002Li et al 8/2000 34-58 (during typhoon) Biscayne Bay, USA 1993 (9.2) (0.4) Valette-Silver et al 1999Charleston Harbor, South Carolina 9/1998-9/1999 Zhang 1996Huanghe Estuary 5/1985, 19863.8-28.8 Zhang 19968/1985, 198617.8-38.8 Changjang 1986(10.6) Elbaz-Poulichet et al 1990Zhang et al 1990Changjiang Estuary 8/2002-5/2003 0.05-6.8 (1.79) Cheng et al 2006 Pearl River Estuary 11/1992 26.7-36.0 (30.7) Rh么ne Estuary, France 3/1984, 7/1987, 7/198814.7-50.7 (29.4) Seyler and Martin 1990Gironde Estuary, France 5/1994 0.2-3.9 (1.8) Michel et al 1997Lena, Russia 9/1989 (2) Martin et al 1993 North Atlantic (surface) 8 Central North Sea 8/19889.73-14.80 (11.39) Millward et al 19969/1989 construct a TDIAs budget for Jiaozhou ...…”
Section: Arsenic Budgetmentioning
confidence: 99%